PESAN KETERBUKAAN KOMUNIKASI KELUARGA PADA SANDWICH GENERATION MELALUI FILM “1 KAKAK 7 PONAKAN” - Irene Navita Soeparmo; Sunarto Sunarto (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2026)
Recently, the phenomenon of the sandwich generation has become increasingly relevant. The reality of family communication in Indonesia, which tend to be more closed, can further intensify the pressures experienced by the sandwich generation. As film served as the representation of reality, this gap is portrayed by a film director, Yandy Laurens, in the film “1 Kakak 7 Ponakan”. This study aims to describe the messages of family communication openness within the sandwich generation as portrayed in the film “1 Kakak 7 Ponakan”, as intended by the story’s writer himself. Employing a qualitative descriptive approach, this research utilizes Schleiermacher’s hermeneutic analysis as its analytical framework. The hermeneutic analysis is conducted through three stages: grammatical analysis, semantic analysis, and textual interpretation. The findings indicate that “1 Kakak 7 Ponakan” conveys messages of family communication openness among the sandwich generation, articulated through the aspects, processes, and impacts of such openness. Communication openness within the family in the film is achieved through the disclosure of personal information ranging from basic to intimate details. This openness, which is exercised within reasonable limits, has a positive impact on the family in the film. These points are represented across eleven selected scenes in the film.